The Therapist's Intuition and Responsiveness: What Makes the Difference between Expert and in Training Gestalt Psychotherapists - Margherita Spagnuolo Lobb; Federica Sciacca; Serena Iacono Isidoro; Santo Di Nuovo (MDPI AG, 2022)
This study aims to investigate the presence of intuition and responsiveness in early students and in experienced students and psychotherapists, which is understood as the ability to integrate bodily sensitivity and cognition of what is experienced with the patient (aesthetic relational knowing-ARK). The study compares how the therapist's felt sense of the phenomenological intersubjective field and aesthetic relational competence differs between a group of experienced students and psychotherapists and a group of beginners. The sample consisted of 128 participants (20 M; 108 F), finally divided into two groups: "experienced students and psychotherapists" and "beginners". The Aesthetic Relational Knowledge Scale (ARKS), a questionnaire consisting of 58 items targeting three factors (empathy, body awareness, and resonance), was administered. Statistical analyses were conducted to assess (i) differences between the two groups (through Student's t and Cohen's d for effect sizes), (ii) the influence of the level of training for each ARK factor using analyses of covariance for testing the possible influence of demographic variables, and (iii) logistic regressions to compare the influence of the three factors of the ARK model on the group variable with groups as a categorical variable. Significant differences between the two groups were found in body awareness and resonance. Body awareness was found to be the variable best discriminating between the beginners and the experienced students and psychotherapists. Despite being non-significant, there is a tendency suggesting that empathy appears more relevant at the beginning of training. The study shows the importance of training for the development of the therapist's intuition and responsiveness, especially in the factors of body awareness and resonance. The results indicate the importance of assessing and supporting the aesthetic and field resonance of therapists in training, increasing quality and depth of the therapist's responsiveness. This study is limited by a correlational design using self-report and on a limited sample, but it shows that the ARKS can monitor the effectiveness of training related to Gestalt therapeutic competencies.